Advances in Immunotherapy and Implications for Current Practice in Non–Small-Cell Lung Cancer. Issue 11 (November 2021) - Steuer, Conor E.; Ramalingam, Suresh S.
Abstract : Treatment options for patients with non–small-cell lung cancer (NSCLC) have improved dramatically in recent years. For decades, harnessing a person's own immune system to fight cancer has been a major area of research in oncology. Recently, these efforts have proven successful with the development of immune checkpoint inhibitors; these agents have now become part of the routine care of NSCLC. Presently, five programmed cell death-1 and programmed cell death-1 ligand 1 inhibitors and one anti–cytotoxic T-cell lymphocyte-4 inhibitor are US Food and Drug Administration–approved in the treatment of NSCLC. These drugs have made a dramatic difference in the lives of patients with NSCLC, although durable benefits are limited to a subset of patients. In this review, we highlight the trials that led to our current treatment practices, discuss areas of active research, and address common clinical issues that have risen as immune therapy has become a mainstay of treatment in NSCLC.